1902
DOI: 10.5962/bhl.title.96729
|View full text |Cite
|
Sign up to set email alerts
|

Seeds and bulbs /

Abstract: It should be sown at the rate of one pound for a space 15x20 feet square. For further directions see above under the word "How." "SHADY NOOK" Lawn Grass Seed per pound 25c; 5 lbs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Its normal value ranges between 4620-11500 U/L in males and 3930-10800 U/L in females. [9] In dementia, this enzyme which establishes dementia is decreased[10] in 94.59% patients. On Hamilton Anxiety Rating Scale, it was observed that 97.80% patients had anxious mood, followed by 96.70% having depressed mood, 96.70% patients having difficulty in concentration and memory and tension.…”
Section: Observation and Resultsmentioning
confidence: 99%
“…Its normal value ranges between 4620-11500 U/L in males and 3930-10800 U/L in females. [9] In dementia, this enzyme which establishes dementia is decreased[10] in 94.59% patients. On Hamilton Anxiety Rating Scale, it was observed that 97.80% patients had anxious mood, followed by 96.70% having depressed mood, 96.70% patients having difficulty in concentration and memory and tension.…”
Section: Observation and Resultsmentioning
confidence: 99%